Development of medical education in Nepal - Dixit, H (Kathmandu University Medical Journal, 2009)
The first institution for training health workers started 75 years ago. Further development of teaching / learning institutions, mainly governmental started from the middle of the 20th Century. It was however with the setting up of the Institute of Medicine (IoM) under TU that training programmes for different grades of health manpower were started. The last two decades has seen an explosion of institutions involved in the training of health personnel. This is possibly because of the huge demand of human resources of health (HRH) not only in Nepal, but worldwide. Various grades of HRH are going out of the country and seeking their livelihood elsewhere. Key words: IoM, BPKIHS, PAHS, HRH doi: 10.3126/kumj.v7i1.1757 Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 8-10